PENGARUH MODEL PEMBELAJARAN SMALL GROUP DISCUSSION (SGD) BERBANTUAN MEDIA PUZZLE BOX TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS III SDN BANDUNGAN 01 - Thohiriyah, Umie Wahidatun; Rizqi, Hesti Yunitiara; Purwanti, Kartika Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the influence of the Small Group Discussion (SGD) learning model assisted by Puzzle Box media on the ability to understand concepts in class III elementary school students. This research uses a quasi-experimental design method with a purposive sampling design. The research subjects were students of class III A and III B at SDN Bandungan 01. Data collection techniques were carried out using tests (pre-test and post-test) and non-tests (observation, questionnaires, unstructured interviews and documentation). Data analysis techniques include normality test, homogeneity test, Independent Sample t-test, and simple linear regression test. The results of the research showed that there was a significant difference in students' conceptual understanding between the experimental group that used the SGD learning model assisted by Puzzle Box media and the control group that did not use it. The average value of students' conceptual understanding in the experimental class (87.28) was higher than in the control class (76.89). Apart from that, there is a significant influence of the SGD learning model assisted by Puzzle Box media on students' ability to understand concepts, with an R Square value of 0.755 or 75.5%. This shows that the SGD learning model assisted by Puzzle Box media can increase students' ability to understand concepts by 75.5%. The conclusion of this research is that the Small Group Discussion (SGD) learning model assisted by Puzzle Box media has proven to be effective in improving the ability to understand concepts in class III elementary school students. The use of Puzzle Box media in the SGD model provides a more interesting and interactive learning experience, so that students are more active in discussing and understanding concepts.